Gambaran Pendidikan Ibu Terhadap Kejadian Karies Gigi Pada Anak Stunting di Desa Pulau Nyiur Kecamatan Karang Intan Kabupaten Banjar Kalimantan Selatan - Bunga Nurwati; Isnawati, Isnawati; Nuryati, Sri (Poltekkes Kemenkes Banjarmasin, 2024)
Stunting is one of the most common forms of malnutrition. This condition can hinder a child's development, including the development of the oral cavity. Children who experience stunting are more vulnerable to dental caries due to changes in the characteristics of saliva. This study aims to understand the relationship between maternal education level and the incidence of dental caries in children with stunting in Pulau Nyiur Village, Karang Intan Subdistrict, Banjar Regency, South Kalimantan. Dental caries in stunted children can be influenced by several factors, including the mother's knowledge and education in maintaining children's dental health and dietary habits. This research uses a quantitative descriptive method with data collected through questionnaires distributed to mothers of stunted children in the village. The results of the study are expected to provide an overview of the impact of maternal education level on the prevalence of dental caries in stunted children, as well as to offer insights for child health improvement programs, particularly in rural areas.